2024
DOI: 10.1002/anie.202315362
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Phosphorescence of Benzils Achieved by Chiral Supramolecular Polymerization

Longyu Guang,
Yi Lu,
Yifei Zhang
et al.

Abstract: In current approaches for circularly polarized phosphorescent materials, the crystallization of chiral phosphors suffers from poor processability, while integrating them into an amorphous polymer matrix results in unsatisfactory chiroptical signals due to the absence of chirality communication. Here, we have developed an innovative strategy through chiral supramolecular polymerization of benzil phosphors facilitated by intermolecular hydrogen bonds. The inherent film‐forming capabilities of non‐covalent supram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In recent years, some organic materials with CPP activity have been prepared. Zhang and co-workers incorporated the achiral phosphorescent chromophore dibenzofuran into a chiral cholesterol substrate, enabling the cholesteric liquid crystal to emit CPRTP . An et al reported that axial chiral chromophores, when doped into the polymer chain through free radical cross-linking polymerization, enabled the amorphous copolymers to exhibit CPRTP …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some organic materials with CPP activity have been prepared. Zhang and co-workers incorporated the achiral phosphorescent chromophore dibenzofuran into a chiral cholesterol substrate, enabling the cholesteric liquid crystal to emit CPRTP . An et al reported that axial chiral chromophores, when doped into the polymer chain through free radical cross-linking polymerization, enabled the amorphous copolymers to exhibit CPRTP …”
Section: Introductionmentioning
confidence: 99%
“…The noncovalent connection renders inherent responsiveness to supramolecular polymers . For example, the strength of hydrogen bonds varies with solvent and temperature, making them suitable for constructing stimuli-responsive supramolecular polymers that react to changes in solvent polarity and heat. Particularly, temperature increases can significantly reduce viscosity, facilitating the processing of supramolecular polymeric materials and enabling applications in inkjet printing or coatings for thermosensitive substrates. , In addition to the inherent responsiveness, another intriguing strategy is to incorporate additional stimuli-responsive units into supramolecular polymers. This allows for tailored responses to specific stimuli such as pH values, , chemical additives, , light, redox, , or mechanical force. Stimuli-responsiveness can modify the intrinsic properties of monomeric building blocks or influence their noncovalent bonding mode.…”
Section: Introductionmentioning
confidence: 99%
“…Attributed to the promising applications in many fields such as 3D display, information encryption, and asymmetric synthesis, chiral luminescent materials with circularly polarized luminescence (CPL) properties have been widely reported in recent years. Typically, CPL materials consist of chiral and chromophore components that interact in various ways. To date, many strategies have been developed to prepare high-performance CPL materials with high luminescence quantum yield and a large luminescence asymmetry factor ( g lum ), such as construction of chiral luminescent liquid crystals, , chiral supramolecular assembly, fluorescence resonance energy transfer (FRET), , and so forth. However, most reported CPL materials mainly focused on the fluorescence, and the research on circularly polarized phosphorescence (CPP) materials is limited.…”
Section: Introductionmentioning
confidence: 99%